The (Mistica) doctor is in communicating health at Suprema dela Iglesia del Ciudad Mistica de Dios - Jabal, Ronaldo F.; Paradina, Katrina Paulette T.; de Vera, Marianne Johann F. (2010)
Throughout history, religion, spirituality, health, and the practice of medicine have been intertwined but are all united in seeking improved health for all. Medical organizations and faith-based institutions consider caring for the sick as their primary mission, sometimes drawing from each other?s knowledge about healing to address patients? concerns. This paper examines the role of spirituality and religion on the health of a populace and explains how a faith-based organization uses spirituality as the foundation for communicating health even as the community avails itself of medical science through the provision of a Barangay health center.